Effectiveness of psychotherapy in adult ADHD: what do patients think? : results of the COMPAS study - Groß, Vivien; Sobanski, Esther (Journal of attention disorders, 2017)
Objective: In the multicenter study Comparison of Methylphenidate and Psychotherapy in Adult ADHD (COMPAS), the efficacy of treatments has been primarily evaluated by observer-rated symptom change. Here, we additionally analyzed the patients’ subjective evaluation of therapy effects. Method: COMPAS compared ADHD-specific group therapy with unspecific clinical management with/without concomitant pharmacotherapy in a four-armed design. Evaluation through the patients’ retrospective perspective was performed after 1 year (post-treatment) and after another 1.5 years (follow-up). Results: In respect to patients’ subjective ratings, ADHD-specific group psychotherapy outperformed unspecific management post-treatment (z = 4.88, p < .0001) and at follow-up (z = 2.90, p = .004). Rank correlations with rater-based symptom change were small to moderate (post-treatment: rs = 0.28, follow-up: rs = 0.16). Conclusion: Therapy evaluation based on the patients’ perspective supports the concept of ADHD-specific group psychotherapy as a potentially useful therapy option in ADHD.